2018
DOI: 10.3390/gels4030068
|View full text |Cite
|
Sign up to set email alerts
|

A Methylcellulose Hydrogel as Support for 3D Plotting of Complex Shaped Calcium Phosphate Scaffolds

Abstract: 3D plotting is an additive manufacturing technology enabling biofabrication, thus the integration of cells or biologically sensitive proteins or growth factors into the manufacturing process. However, most (bio-)inks developed for 3D plotting were not shown to be processed into clinically relevant geometries comprising critical overhangs and cavities, which would collapse without a sufficient support material. Herein, we have developed a support hydrogel ink based on methylcellulose (mc), which is able to act … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…The temperature-dependent gelation point of mc gels decreases with increasing concentration. 21,41,44 In comparison to 6% and 8%, a 10% mc ink with the lowest gelation point demonstrated best printability, 41 indicating that the printability is improved when mc is processed in sol state near the gelation point. The gelation of mc can be influenced by the presence of diluted salts.…”
Section: Biomaterials Science Minireviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The temperature-dependent gelation point of mc gels decreases with increasing concentration. 21,41,44 In comparison to 6% and 8%, a 10% mc ink with the lowest gelation point demonstrated best printability, 41 indicating that the printability is improved when mc is processed in sol state near the gelation point. The gelation of mc can be influenced by the presence of diluted salts.…”
Section: Biomaterials Science Minireviewmentioning
confidence: 99%
“…Due to this reason, commercially available mc usually is characterized by its viscosity (of a 2% solution at 20°C) and the molecular weight is a recalculated value, which does not allow drawing conclusions for the distribution of the molecular weight. We found that most studies [32][33][34][35][36][37][38][39][40][41] used an mc with a given viscosity of 4000 mPa s (M n ≈ 86 kDa); 30 these studies have in common to have achieved printing of multiple layers and only limited collapse of predesigned macropores. Other studies 42,43 reported about the use of mc with a given viscosity of 15 mPa s (M n ≈ 14 kDa) and found significant improvements of the printed shape fidelity in presence of mc compared to mc-free controls, but those structures lacked the evidence of multiple layer stacking.…”
Section: Biomaterials Science Minireviewmentioning
confidence: 99%
See 3 more Smart Citations